Analisis Jaminan Hari Tua Pekerja pada Dinas Pencegahan dan Pemadam Kebakaran (P2K) UPT 1.0 Medan Tuntungan, Sumatera Utara - Ginting, Esekiel Pranata; Purba, Rami Santia; Ginting, Trifosa Irena; Siregar, Hairani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The implementation of social security programs is a state obligation to provide comprehensive protection for the social and economic welfare of all its citizens, especially in developing countries such as Indonesia. Social security programs that generally use the principle of funded social security are designed to ensure the fulfillment of basic community needs and protect against unexpected life risks. In Indonesia, one of the agencies that plays a role in organizing social security is BPJS Ketenagakerjaan, which provides employment protection for formal and informal sector workers. The Old Age Security (JHT) program by BPJS Ketenagakerjaan is designed to provide financial protection for workers who have reached retirement age or have stopped working. This study focuses on the implementation of the Old Age Security Program at the Fire Prevention and Extinguishing Service (P2K) UPT 1.0 Medan Tuntungan. Based on the results of observations and in-depth interviews, the implementation of JHT in this service has been in line with applicable regulations. This study aims to highlight the importance of social security in supporting worker welfare, as well as the role of the government in increasing national productivity through adequate social protection programs.